2007
DOI: 10.1159/000098468
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Motor Symptoms upon the Quality of Life of Patients with Parkinson’s Disease

Abstract: We studied the impact of various motor and nonmotor symptoms upon quality of life in patients with Parkinson’s disease (PD). The study comprised 110 patients with PD (age: 68.6 years, course of the disease: 7.6 years). The Unified Parkinson Disease Rating Scale (UPDRS; I–IV) and Parkinson’s Disease Questionnaire (PDQ-39) were recorded. We recorded the correlations between years of disease and UPDRS IV, as well as PDQ-39 and UPDRS I, II, III and IV. Introduction of all variables into a linear regression model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 40 publications
(26 reference statements)
8
66
1
1
Order By: Relevance
“…These results corroborate the findings of other researches that indicate the close association between motor symptoms measured by the UPDRS, HY and SE, and a poor QoL in individuals with PD [8][9][10][11][12] . Lyons et al 30 found that postural instability, gait abnormalities and bradykinesia assessed by means of questions from the motor section of the UPDRS have the greatest impact on the QoL.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These results corroborate the findings of other researches that indicate the close association between motor symptoms measured by the UPDRS, HY and SE, and a poor QoL in individuals with PD [8][9][10][11][12] . Lyons et al 30 found that postural instability, gait abnormalities and bradykinesia assessed by means of questions from the motor section of the UPDRS have the greatest impact on the QoL.…”
Section: Discussionsupporting
confidence: 91%
“…The QoL in PD patients includes the individual's symptoms and physical functioning, as well as psychosocial variables 26 . Although many studies demonstrated that the motor symptoms contribute to the worsening of the perception of QoL in individuals with PD, these investigations predominantly correlated the items of the UPDRS with the dimensions from the PDQ-39 [10][11][12][13] . Therefore, the aim of our study was to specifically assess the balance and the walking capacity of PD patients through instruments usually used in clinical practice of the Physiotherapy and to correlate the findings with the QoL perception of these individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations